Altered expression of the miRNA processing endoribonuclease Dicer has prognostic significance in human cancers. (January 2013) - Pellegrino, Loredana; Jacob, Jimmy; Roca-Alonso, Laura; Krell, Jonathan; Castellano, Leandro; Frampton, Adam E
Evaluation of : Jafarnejad SM, Ardekani GS, Ghaffari M, Martinka M, Li G. Sox4-mediated Dicer expression is critical for suppression of melanoma cell invasion. Oncogene doi:10.1038/onc.2012.239 (2012) (Epub ahead of print). Several studies have implicated miRNAs in the initiation and progression of human cancers. Examining the biogenesis pathways that generate these important regulatory molecules has revealed new mechanisms for tumor development. Altered expression of the endoribonuclease Dicer in many tumors has given new hope to unraveling the complex relationship between miRNA processing and cancer. This may provide further insight into mechanisms for targeting multiple genes that are critical for the malignant phenotype of several cancers. The evaluated article demonstrates that Dicer is transcriptionally regulated by Sox4 and reduced levels of this transcription factor consequently leads to a reduction in expression, and therefore deregulation of cancer-related miRNAs in melanoma. Reduced Dicer expression in malignant melanoma is an independent predictor of poor survival. In this review, we assess the prognostic significance of Dicer expression in different tumor types.